ANALISIS YURIDIS PENGELOLAAN ANGKUTAN MASSAL TRANSMETRO DIKAITKAN DENGAN UPAYA PENINGKATAN PENDAPATAN ASLI DAERAH DI KOTA PEKANBARU - Budi, Dio Prasetyo; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Management is a peroses starting from planning, arrangement, supervision, driving up to the process of realization of goals. The term pengelolahan own closely related to the part of procurement activities. Pengelolahan is a form of translation of words derived from the English that is memement. In pengelolahan there is one crucial activity that is the maintenance of mass transports trasmetro this is a form of procurement of goods and services that can attract people to choose a safe transportation, convenient, smooth and fast, especially urban places in the city pekanbaru. Trasmetro mass transit is also able to provide its own input in increasing the original income of the region, especially the new city.In this case the research used is sociological juridical research that is research by looking at the legislation - the legislation and see the reality of the field. In this case the sociological juridical approach greatly influences this research because this research refers to Law Number 22 Year 2009 on Road Traffic and Government and Government Regulation Number 74 Year 2014 About Road Transportation, and Regulation of the Minister of Home Affairs Number 61 Year 2007 On the Technical Management Guideline for Left of Regional Public Service Agency which is directly related to this research. This study was conducted at the Department of Transportation and PD (Pekanbaru City Development Company), while the population and sample are the whole parties related to the problems studied in this study, data sources used, primary data, secondary data, tertiary data, collection techniques Data by interview observation and literature study.From the results of this study the problems that occur have three main things that can be concluded. Firstly, the lack of communication between Pekanbaru City Government and City Transportation Office Pekanbaru in conducting Trasmetro Mass Transit Management in Pekanbaru City, in this case Management provided by PD Development did not take the result of sales service public service to society have contract to assist in doing transportation management Temporary mass that is in the year 2013 - 2016. Then in 2016 Transportation Department as the operator to overhaul the problem Mass Transport with the transfer of management from the PD Development back to the Department of Transportation because the Department of Transportation program budget spending 2017 to BLUD (Badan Layanan Umum Area). Second, Efforts by establishing good communication, improving the quality, provosionalitas, between the government of Pekanbaru City with the Department of Transportation. Suggestion writer, understand in doing service service to society, can give information disclosure about mass transit of trasmetro as public service to society, it is suggested to give solution for problem in field of facility and infrastructure. And to better listen to the aspirations and expectations of the community.Keywords: Management - Regulation - Trasmetro Mass Transit